FEASIBILITY ANALYSIS OF THE ERGONOMIC PET HARNESS FASHION INDUSTRY REVIEW MARKET, VALUE, AND FINANCIAL ASPECTS - Nasution, Anita Hakim; Baskara, Dominggo Bayu; Hidayat, Alifiansyah Arrizqy; Olivia, Tracy; Salsabila, Anindya Salwa; Mahfud, Rifqi Arif (Jurnal Bisnis dan Keuangan, 2025)
This study aims to analyze the business feasibility of ergonomic pet harnesses in Indonesia from market, product value, and financial aspects. With the growing number of pet owners in Indonesia, pet harness products have become a crucial necessity for those who prioritize safety and comfort. This study utilizes capital budgeting methods, including Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) analysis, to assess financial feasibility. To achieve a return above the Minimum Attractive Rate of Return (MARR) of 13%, annual sales must target at least 2,119units at a price of Rp211,125 per unit, with sales growth of 10% per year. BirkinPet targets sales of 2,200 units per year, making this plan feasible, with a projected NPV of Rp72,175,425, an IRR of 32%, and a payback period in the 5th year. The study results show that the business is feasible with sales projections exceeding the minimum target. Recommendations include expanding the market through digital marketing strategies and enhancing product innovation.